Effects of initial surface topography and contact regimes on tribological behavior of AISI-52100/AA5083 materials' pair when reciprocating sliding. (March 2018) - Elwasli, Fatma; Mzali, Slah; Zemzemi, Farhat; Mkaddem, Ali; Mezlini, Salah
Highlights: Lubricated and dry sliding tests were conducted on AA5083/AISI-52100 material pair. The effect of initial surface topography on the wear and friction behavior was discussed. RS approach was applied to correlate crater area, cycle number and mean absolute profile slope. The formation of BUL improve contact condition and provokes transition in wear mechanisms. Analysis of crater area contributes for controlling friction and wear when sliding dry. Abstract: This paper discusses the effect of surface topography and lubrication on the tribological behavior of AA5083 alloy for wide range of average roughness, R a . Reciprocating sliding tests were conducted under lubricated and dry regimes over different pre-textured surfaces using AISI-52100 steel ball under two contact pressures. Scanning Electron Microscope (SEM) and profilometer were employed for characterizing wear land and type. Particularly, the effect of the mean absolute profile slopeΔ a of AA5083 plates on friction and wear was investigated within an early repetitive sliding stage. Experimental results show that a close correlation was found between the tribological behavior and the mean absolute slope, Δ a, contrary to the average roughness, R a, which shows a partial link. From SEM inspections, dry sliding correlates with the generation of ploughing over aluminum topographies, and with the formation of Built-Up Layer (BUL) due to adhesion over steel ball. However, lubrication, transforms material removal process over the ball from adhesion to abrasion which affects inevitably the initial topography. The evolution of crater area S − reflects high sensitivity toΔ a . In order to predict the wear evolution, a mathematical model taking into account the impact ofΔ a and the number of sliding cycles ( N ) was developed using Response Surface Method (RSM). Graphical abstract: Predicted crater area vs. the number of cycles and mean absolute profile slope obtained using RS approach. (a) Smooth, and, (b) rough surfaces at dry conditions, and, (c) Smooth, and, (d) rough surfaces at lubricated conditions.